2014
DOI: 10.1104/pp.114.243360
|View full text |Cite
|
Sign up to set email alerts
|

TGA Transcription Factors Activate the Salicylic Acid-Suppressible Branch of the Ethylene-Induced Defense Program by Regulating ORA59 Expression    

Abstract: Salicylic acid (SA), a hormone essential for defense against biotrophic pathogens, triggers increased susceptibility of plants against necrotrophic attackers by suppressing the jasmonic acid-ethylene (ET) defense response. Here, we show that this diseasepromoting SA effect is abolished in plants lacking the three related TGACG sequence-specific binding proteins TGA2, TGA5, and TGA6 (class II TGAs). After treatment of plants with the ET precursor 1-aminocyclopropane-1-carboxylic acid (ACC), activation of all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 59 publications
(85 reference statements)
4
121
0
2
Order By: Relevance
“…Additional experiments demonstrated that ET can override NPR1 dependency of SA-JA antagonism, indicating that biotic induction of ET modulates the interaction between SA and JA pathways (Leon-Reyes et al, 2010b). Two recent studies discovered that SA treatment promotes ORA59 protein degradation (Van der Does et al, 2013) and inhibit ORA59 expression (Zander et al, 2014), providing the first clues on how gene expression from the ERF branch of the JA pathway is suppressed.…”
mentioning
confidence: 99%
“…Additional experiments demonstrated that ET can override NPR1 dependency of SA-JA antagonism, indicating that biotic induction of ET modulates the interaction between SA and JA pathways (Leon-Reyes et al, 2010b). Two recent studies discovered that SA treatment promotes ORA59 protein degradation (Van der Does et al, 2013) and inhibit ORA59 expression (Zander et al, 2014), providing the first clues on how gene expression from the ERF branch of the JA pathway is suppressed.…”
mentioning
confidence: 99%
“…For example, synergism between JA and ethylene signaling ensures effective induction of plant defenses directed against necrotrophic pathogen attack (Memelink, 2009). Moreover, the JA/ethylene and SA signaling pathways negatively influence each other to prioritize specific defense outputs in plant-pathogen interactions (Koornneef and Pieterse, 2008;Zander et al, 2014). JA biosynthesis and signaling is strongly induced by P. syringae infection in inoculated leaves.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of SA, the same TGAs have a role in SA-mediated antagonism of ERF branch signaling. The TGAs can directly target the activation sequence-1 (as-1) promoter sequence in the ERF transcription factor gene ORA59, thereby regulating its expression (Zander et al, 2014). Possibly through SA-induced glutaredoxins such as GLUTAREDOXIN480 (GRX480) that interact with TGA transcription factors, expression of ORA59 is suppressed (Zander et al, 2012;Caarls et al, 2015).…”
Section: Effect Of Et On Sa-ja Cross Talkmentioning
confidence: 99%